STUDENTS’ ERROR ANALYSIS IN WRITING RECOUNT TEXT BASED ON BETTY SCHRAMPFER AZAR THEORYAT MTs AL MUHSIN METRO IN ACADEMIC YEAR 2021/2022 - Aulia Hanifah Qomar; Fitria Nabila Ulfah (Universitas Muhammadiyah Metro, 2023)
The research aimed at analyzing the errors made by students in writing recount text of the Eighth Grade Students of MTs Al Muhsin Metro In The Academic Year 2021/2022. The subject of this research consists of 34 students in VIII A. The objectives of the study were (1)To know kinds of errors in writing recount text made by the students at the eighth grade MTs Al Muhsin Metro in the Academic Year 2021/2022. (2)To know the dominant error in writing recount text made by the students at the eight grade MTs Al Muhsin Metro in the Academic Year 2021/2022. This study used qualitative research, with a descriptive method. The instruments of the research was a test and documetation for the students. The errors were collected, identified, and classified based on guiding of writing by Betty Schrampfer Azar theory. It was specified by fourteen types of errors they are singular-plural, word form, word choice, verb tense, add a word, omit a word, incomplete sentence, spelling, punctuation, capitalization, article, and run-on sentence. The result shows that the errors made by student were 1) spelling as the dominant error with a total 31 errors or 23,48%. 2) Verb tense with a total 25 errors or 18,94%. 3) Capitalization with a total 16 errors or 12,12%. 4) Meaning not clear with a total 9 errors or 6,82%. 5) Word choice with a total 8 errors or 6,06%. 6) Word order with a total 7 errors or 5,30%. 7) Word form with a total 6 errors or 4,55%. 8) Punctuation 7 errors or 5,30 %. 9) Article with a total 5 errors or 3,79%. 10) Run on sentence with a total 5 errors or 3,79%. 11) Singular plural with a total 4 errors or 3,03%. 12) Add a word with a total 4 errors or 3,03%. 13) Omit a word with a total 3 errors or 2,27%, and 14) incomplete sentence with a total 3 errors or 2,27%.